Karakteristik Pasien Penyakit Jantung Koroner yang Menjalani Bedah Pintas Arteri Koroner di Medan 2022 - Fahriza, Muhammad; Siregar, Yasmine Fitrina (SCRIPTA SCORE Scientific Medical Journal, 2024)
Background: Coronary Heart Disease (CHD), the leading global cause of death, stems from artery constriction due to fat deposition and vessel stiffness, leading to insufficient blood flow to the heart muscles. Despite numerous studies on CHD characteristics, none reflect the latest data specific to North Sumatra, contributing to 32% of global deaths. Objective: To describe the characteristics of CHD patient that underwent coronary artery bypass graft (CABG) in 2022 at RSUP Haji Adam Malik Medan. Methods: This descriptive research with cross-sectional design was done to CHD patients that underwent CABG operation with total sampling technique and used medical record data that was taken and grouped to characteristics before, during, and after the surgery. Results: Out of 48 complete medical records, majority of patients are in the age range of 48-65 years old (73%), male gender (85.4%), hypertension and/or type 2 diabetes patient (70.9%), abnormal lipid profile (93.8%), operation duration 240309 minutes (66.7%), normal ejection fraction (56.3%), in use of cardiopulmonary bypass machine (on pump) during operation (54.2%), CPB time 118-159 minutes (53.8%), Aox time 59-88 minutes (50%), in use of 3 grafts (56.3%), normal kidney function after the operation (83.3%), abnormal routine blood profile (53.88%), and without complications (66.7%). Conclusion: In this study, the average age of patients was 56, mostly male, with abnormal lipid profiles. The prevalent comorbidities were hypertension and/or type 2 diabetes. Operations averaged 284.75 minutes, using 3 grafts, with 43.7% having lowered ejection fraction. Arrhythmia was the most common postoperative complication. Keyword: CABG, Characteristics, CHD Latar Belakang: Penyakit Jantung Koroner (PJK), penyebab utama kematian global, disebabkan oleh penumpukan lemak dan/atau kekakuan pembuluh darah, mengurangi perfusi otot jantung dan menyumbang 32% angka kematian dunia. Banyak penelitian karakteristik pasien PJK, tetapi kurangnya data terbaru karakteristik PJK di Sumatera Utara menjadi perhatian. Tujuan: Untuk mendeskripsikan karakteristik pasien PJK yang menjalani bedah pintas arteri koroner pada tahun 2022 di RSUP Haji Adam Malik Medan. Metode: Penelitian deskriptif dengan desain cross-sectional ini dilakukan pada pasien PJK yang menjalani operasi bedah pintas arteri koroner (BPAK) dengan teknik total sampling serta menggunakan data rekam medis yang diambil dan dikelompokkan menjadi karakteristik sebelum, selama, dan setelah operasi. Hasil: Dari 48 rekam medis lengkap, pasien paling banyak pada kelompok usia 48-65 tahun (73%), jenis kelamin laki-laki (85,4%), penderita hipertensi dan/atau DM tipe 2 (70,9%), profil lipid abnormal (93,8%), durasi operasi 240-309 menit (66,7%), fraksi ejeksi normal (56,3%), menggunakan mesin jantung paru (on pump) selama operasi (54,2%), CPB time 118-159 menit (53,8%), Aox time 5988 menit (50%), menggunakan 3 graft (56,3%), fungsi ginjal normal paska bedah (83,3%), profil darah rutin abnormal (58,33%), dan tidak mengalami komplikasi (66,7%). Kesimpulan: Pasien penelitian ini rata-rata berusia 56 tahun, didominasi oleh laki- laki, mayoritas memiliki profil lipid abnormal, dengan komorbid terbanyak adalah hipertensi dan/atau DM tipe 2. Mayoritas pasien tidak mengalami komplikasi paska pembedahan. Komplikasi tersering adalah aritmia. Kata Kunci: BPAK, Karakteristik, PJK